RESEARCHING LEARNING STRATEGY TRAINING IN ENGLISH CAMPS: ACTS AND FACTS - Widya Rizky Pratiwi (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
As English grows as a foreign language in Indonesia, which is rarely used daily, learning strategy training might be one innovation to help students acquire the target language quickly. This study aimed to research the implementation of learning strategy training in English camps and understand the effect of the training on the student’s ability to solve their learning problems, especially in speaking English. It was a qualitative design with a case study approach. This research was conducted in the English village of Kampung Inggris Pare. It limited the investigation of learning strategy training in English boardings or camps. Four participants consisting of three students and one instructor were selected purposely. The data were gathered by conducting direct observations, interviews, and photos. They were then analyzed in six steps starting from preparing raw data materials to interpreting the meaning of the theme into qualitative descriptions. The results show that the instructor trained two domains of students' soft skills: affective and cognitive. From the affective side, the instructor encouraged students' motivation to stay enthusiastic, not hesitate to speak, and are not scared of making mistakes. While from the cognitive side, the instructor trained students to learn English through their hobby or passion, such as through a song or movie for those who love music or watching. In fact, students could find and develop their own learning strategies based on their learning style and